Reduced amygdala responsivity during conditioning to trauma-related stimuli in posttraumatic stress disorder - Diener, Slawomira; Ruttorf, Michaela; Schmahl, Christian; Flor, Herta (Psychophysiology, 2016)
Exaggerated conditioned fear responses and impaired extinction along with amygdala overactivation have been observed in posttraumatic stress disorder (PTSD). These fear responses might be triggered by cues related to the trauma through higher-order conditioning, where reminders of the trauma may serve as unconditioned stimuli (US) and could maintain the fear response. We compared arousal, valence, and US expectancy ratings and BOLD brain responses using fMRI in 14 traumatized persons with PTSD and 14 without PTSD (NPTSD) and 13 matched healthy controls (HC) in a differential aversive conditioning paradigm. The US were trauma-specific pictures for the PTSD and NPTSD group and equally aversive and arousing for the HC; the conditioned stimuli (CS) were graphic displays. During conditioning, the PTSD patients compared to the NPTSD and HC indicated higher arousal to the conditioned stimulus that was paired with the trauma picture (CS+) compared to the unpaired (CS−), increased dissociation during acquisition and extinction, and failure to extinguish the CS/US-association compared to NPTSD. During early and late acquisition, the PTSD patients showed a significantly lower amygdala activation to CS+ versus CS− and a negative interaction between activation in the amygdala and dorsolateral prefrontal cortex (PFC), while NPTSD and HC displayed a negative interaction between amygdala and medial PFC. These findings suggest maladaptive anticipatory coping with trauma-related stimuli in patients with PTSD, indicated by enhanced conditioning, with related abnormal amygdala reactivity and connectivity, and delayed extinction.